Effect of polyamide-12 material compositions on mechanical properties and surface morphology of SLS 3D printed part / Mohammad Rafi Omar … [et al.] - Omar, Mohammad Rafi; Abdullah, Muhammad Ilman Hakimi Chua; Alkahar, Mohd Rizal; Abdullah, Rohana; Abdollah, Mohd Fadzli; Subramaniam, Mahananthan; Ibramsa, Rizwana Seeni (Universiti Teknologi MARA, 2022)
Despite the fact that many 3D printed products have been developed, there are still issues with the printed product’s physical properties and surface morphology. This study examines the effects of significant Selective Laser Sintering (SLS) 3D printer parameters on the material strength of Polyamide-12 (PA-12). A variety of virgin materials, reheat materials, and recycled materials were used for the PA-12 material compositions. The test specimens were prepared at different process parameters and material composition percentages using the SLS 3D printer. The tensile strength, surface roughness, and surface morphology were tested. These samples were tested in accordance with ASTM D638-(IV) for tensile strength and roughness using a 10 mm x 10 mm coated sample prepared for scanning in an electron microscope. The tensile test results showed that the composition of the 100% virgin (CP1) material samples appeared to be stiffer, with a lower plastic deformation at maximum tensile stress (45 MPa) and a smoother surface roughness (10.75μm). Furthermore, the SEM results showed that the specimens were partially melted with a significant amount of PA-12 powder before being sintered and coalesced.